Pengaruh kemampuan verbal dan kognitif dalam mengerjakan soal cerita matematika di sekolah dasar - Asdar, Andi Fathul (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Story problems have their own difficulties in solving them. For students, story questions must be understood verbally and cognitive abilities are needed to solve them. This research aims to determine the effect of verbal and cognitive abilities in working on math story questions. This research is a quantitative research. The sample in this study were students of grade IV SDI Datuk Ribandang, amounting to 20 people. Data collection was done by giving tests. The data obtained were analyzed using multiple regression test. The results obtained showed that verbal and cognitive abilities had an effect on students' abilities in working on math story questions.